2018
DOI: 10.15171/ijhpm.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Malaria Knowledge and Treatment Practices in Enugu State, Nigeria: A Qualitative Study

Abstract: Background: Malaria accounts for 60% of outpatient visits in Nigeria. The aim of the study was to assess the knowledge of malaria and its treatment practices in Enugu state, Nigeria. Methods: Qualitative data was collected through the use of focus group discussions (FGDs), from six villages three each from urban and rural areas of Enugu state, Nigeria. A total of 18 FGDs involving 189 participants were conducted and data on place of treatment for malaria and drug of choice for malaria treatment were collected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 31 publications
5
22
0
Order By: Relevance
“…Behaviour change communication (BCC) strategies that address community level misconceptions and social beliefs on ITNs use could improve use among all population groups in Ghana. Studies in Ethiopia, Nigeria, Tanzania, Zambia, and Zimbabwe [2226] found community and individual level factors that influence knowledge-practices differences, as found in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…Behaviour change communication (BCC) strategies that address community level misconceptions and social beliefs on ITNs use could improve use among all population groups in Ghana. Studies in Ethiopia, Nigeria, Tanzania, Zambia, and Zimbabwe [2226] found community and individual level factors that influence knowledge-practices differences, as found in Ghana.…”
Section: Discussionmentioning
confidence: 99%
“…A qualitative study revealed the various perceived causes of malaria by individuals such as some people say if the rain beats you, you will have malaria; at times they also say it is a spiritual arrow from somebody that hates you; when they [children] walk under the sun and play in the sun it also causes this sickness of malaria; when you take oil (palm oil) too much, you get malaria (Oladimeji et al, 2018). According to Uzochukwu et al (2018) in a study conducted in Eastern Nigeria, even though the community members had good knowledge of malaria symptoms, certain misconceptions still existed like the reliance on yellowish urine, bitterness of mouth, which are very subjective symptoms of malaria in adults and in children. In a similar study carried out among married men by Padonou et al (2018) in Southern Benin, it was found that 9.3 % and 9.4% attributed the cause of malaria to the sun and from body weakness respectively.…”
Section: Perception On Malaria Among Married Menmentioning
confidence: 99%
“…Malaria remains a world health problem with millions of cases each year, especially in African countries, and malaria-associated deaths reached 445,000 with nearly half the world's population at risk of the infection 1. In Nigeria, malaria is responsible for 25% infant and 30% childhood mortality, and it is the country with the highest number of malaria cases,2 with 60% of outpatients and 30% hospitalization attributed to malaria 3. Infants under 5 years, pregnant women, patients with HIV/AIDS, nonimmune migrants, and travelers have high level of susceptibility to malaria 4…”
Section: Introductionmentioning
confidence: 99%